The Making of the Modern Iranian Women - Roksana Bahramitash (International Institute of Islamic Thought, 2004)
The book, a detailed historical examination of an important era of contemporary Iran’s history, documents a variety of late-nineteenth-century views on “the women’s question.” Amin’s attempt to review its historical background is an excellent gender-perspective analysis of the political atmosphere existing before Iran’s constitutional revolution of 1906-08. The intellectual debate ranged enormously during this period. For example, the atheist Akhundzadeh blamed Islamic and Turkmen rule (Central Asians tribal rulers who had invaded Iran throughout Iranian history) for their situation. Meanwhile, the Babist Kermani, who called Iranian women “the living dead,” saw their enslavement as the result of the corrupted Arab culture transmitted through Islam. The example of such “progressives” as Taghizadeh, who followed western ideas and used the most racist and sexist arguments against women’s equality, presents an interesting aspect of westernization, which is brought up in the book. Alongside these different views, Amin documents a different and equally valuable late-nineteenth-century response that sought equality for women within Islam. This trend, similar to that of Qasim Amin of Egypt, includes as its most notable example Jamal al-Din Asadabdi, who supported a modern interpretation of Islam that included gender equality. Mirza Malkam Khan, publisher of Ghanon (The Law), a newspaper printed in exile, was the first person to transform the “women’s question” from an elite discussion to a matter of Iranian public discourse through the press. He argued that women must be treated as human beings with the same dignity that was accorded to men. Amin delineates two responses to the women’s question: a misogynist view that is best illustrated by Ta’dib al Nesvan (Disciplining Women), published during 1882-89, and a reaction to it written by Bibi Khanom Astarabadi, authoress of Ma’ayb al Rejal (The Vice of Men). Astarabadi (in some ways she can be called the first Muslim feminist) condemned such misogynous practices as infidelity and temporary marriage, as well as the drinking, gambling, and pedophilia practiced by some men. The most interesting part of the book is the author’s discussion of Reza Shah and his break with the Qajar dynasty. Reza Shah imposed his ...